Ramayana for the Millennial Generation - Ni Kadek Suartini; I Gede Suwantana (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
This study originates from the issue of how Ramayana, as a classical epic, remains relevant and understood by the millennial generation living in the digital era and an ever-evolving culture. Changes in information consumption patterns and the increasing critical awareness of young generations regarding social issues, including gender equality and moral justice, pose challenges in preserving the traditional values of this epic. This research employs a qualitative approach using virtual ethnography methods to analyze how millennials access, comprehend, and interpret Ramayana within the context of modern life. The findings reveal that adaptations of Ramayana in popular media such as animated films, graphic novels, web series, and interactive games play a significant role in introducing the epic to young audiences in a more engaging and comprehensible manner. Additionally, many millennials are more interested in the philosophical and spiritual aspects of Ramayana, particularly the concepts of dharma and karma, which are considered relevant in facing moral dilemmas and decision-making in the modern era. However, this study also identifies criticisms regarding morality and gender roles in Ramayana, especially concerning the treatment of female characters like Sita. Discussions within digital communities play a crucial role in shaping new understandings and enabling reinterpretations of the story to align with social justice principles. Thus, this study asserts that Ramayana is not merely a static cultural heritage but continues to evolve through adaptation and reinterpretation, ensuring its relevance for the millennial generation.